P033 Randomised controlled trial on the efficacy of Audio-visual Health Educational materials on CPAP ADherence: The AHEAD trial. (7th October 2021) - Ellender, C; Samaranayake, C; Duce, B; Boyde, M; Winter, S; Hukins, C
Abstract: OSA is a prevalent chronic disease with significant health implications, for which achieving >4 hours/night on continuous positive airway pressure (CPAP) is essential for effective treatment. Educational videos to improve CPAP adherence are of interest as a low-cost intervention, however trials have shown mixed results. This study aimed to compare CPAP usage following standard of care education (SOCE), with the usage following the addition of educational videos, customised to incorporate low health literacy communication, motivational and self-efficacy techniques. Methods: Adults with OSA recommended treatment with CPAP, were recruited and randomised in a single blinded method, to watch short educational videos following their in laboratory CPAP study or SOCE. The primary outcome was CPAP usage at 2mths and secondary outcomes were usage at 12mth and proportion of patients with adequate usage >4hrs/night. Results: 195 patients met the eligibility criteria and were randomised to video education (n = 96) or to SOCE (n = 99). There was no significant difference in compliance at 2mths (median usage 1.7hrs IQR 0–6.2 SOCE, 4.4hrs IQR 0–6.7 video education p = 0.1), however at 12mths there was increased usage in the video education arm (median 0hrs IQR 0–5.4 standard of care, 3.8hrs IQR 0–6.87 p = 0.05). The proportion with adequate CPAP usage >4hrs/night at 12mths was higher in the video education group (33, 33% versus 48, 50% p = 0.01). Conclusions: Long-term adherence to CPAP is enhanced by the addition of educational videos that incorporate low health literacy communication and motivational techniques, compared to SOCE.